2023
DOI: 10.1371/journal.pone.0281108
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the views of Singapore junior doctors on medical curricula for the digital age: A case study

Abstract: This study aims to explore the perspectives of medical trainees on the impartation of digital competencies in Singapore’s medical school curricula. It also considers how the medical school experience can be strengthened in order to bridge potential gaps in the integration of these competencies in the local curricula. Findings were drawn from individual interviews with 44 junior doctors from Singapore’s public healthcare institutions including hospitals and national specialty centers. House officers and residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Notwithstanding these developments, and despite being a small country with only three medical schools, it has been challenging to implement national-level initiatives and standardized learning objectives for training medical students in DHC . Furthermore, there is a disconnect between medical school training and clinical practice, as reported by the leaders of its medical schools, clinical educators and junior doctors (Zainal, 1 , et al, 2023;. Speci cally, these stakeholders shared that medical students are insu ciently prepared to utilize digital technologies in clinical practice due to their limited exposure to these technologies in medical school.…”
Section: State Of Digitalization and Digital Training Among Medical S...mentioning
confidence: 99%
See 2 more Smart Citations
“…Notwithstanding these developments, and despite being a small country with only three medical schools, it has been challenging to implement national-level initiatives and standardized learning objectives for training medical students in DHC . Furthermore, there is a disconnect between medical school training and clinical practice, as reported by the leaders of its medical schools, clinical educators and junior doctors (Zainal, 1 , et al, 2023;. Speci cally, these stakeholders shared that medical students are insu ciently prepared to utilize digital technologies in clinical practice due to their limited exposure to these technologies in medical school.…”
Section: State Of Digitalization and Digital Training Among Medical S...mentioning
confidence: 99%
“…The participants also shared that more evidences on the effectiveness of digital technologies and their impacts on patient care would help to accelerate the uptake of these technologies in the healthcare sector. This is crucial since past study has shown that the perceived gradual adoption of digital technologies in the local healthcare industry could act as a barrier to the training of DHC (Zainal, 1 , et al, 2023). However, evidence-based research, at least in the local context, is still lacking (OL1).…”
Section: Need For More Evidences On the Effectiveness Of Digital Tech...mentioning
confidence: 99%
See 1 more Smart Citation